625. Sustained Efforts Improve Adherence to Monitoring for Solid Tumor Patients Discharged on Outpatient Parenteral Antimicrobial Therapy (OPAT) at a Comprehensive Cancer Center. (31st December 2020) - Robins, Alison; McDaneld, Patrick; Garnes, Natalie J Dailey; Rowan, Meagan; Bartek, Jalen
Abstract: Background: OPAT helps reduce hospital length of stay, but 1 in 4 patients is readmitted within 30 days of discharge. Follow up < 30 days after discharge and laboratory monitoring during therapy have been shown to reduce hospital readmissions. However, few OPAT studies have included patients with malignancies, who may not experience the same benefits due to increased risks for hospital admission and infection related to antineoplastic therapy. We started an OPAT program to increase laboratory monitoring and clinic follow up among patients with solid tumors, attempting to also decrease readmissions. Methods: We obtained demographic data and baseline frequencies of laboratory monitoring, ID clinic follow up, 30-day OPAT-related readmissions, Emergency Center (EC) visits, and deaths by retrospective chart review. We conducted multiple interventions from June 2018-January 2020: clarifying physician recommendations for laboratory monitoring and follow up by using a standardized electronic medical record template, communicating recommendations to case management, and changing the lab ordering workflow. We compared frequencies after interventions to baseline by using Fisher's exact test. Results: Most commonly observed malignancies in our patient cohort included genitourinary, breast, gastrointestinal, gynecologic, and head and neck. The most commonly treated infections included abscess, bacteremia, and skin and soft tissue. The percentage of patients without recommended lab monitoring decreased from 32.3% to 15.3% (p=0.03). We observed trends toward improved ID clinic follow up (54.8% to 71.8%; p=0.12) and decreased 30-day OPAT-related readmissions from 16.7% to 8.6% (p = 0.17). We observed no difference in mortality or EC visits. Conclusion: OPAT-treated infections in our solid tumor patient cohort differed from those reported commonly. Through continued interventions, we improved lab monitoring rates among solid tumor patients with trends toward improved ID clinic follow up and decreased readmission rates. Our findings suggest that despite competing reasons for hospital readmission, OPAT may still benefit this population. Disclosures: All Authors : No reported disclosures